QUANTITATIVE DETERMINATION OF CRIZOTINIB IN HUMAN PLASMA WITH HIGHPERFORMANCE LIQUID CHROMATOGRAPHY AND ULTRAVIOLET DETECTION - NALANDA REVU, BABY; RAO ATLA, SRINIVASA; DANNANA, GOWRI SANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: A rapid, sensitive, selective, and reproducible reversed-phase high-performance liquid chromatographic method has been developed and validated for the determination of crizotinib (CRZ), a tyrosine kinase inhibitor for targeted therapy of anaplastic lymphoma kinase-positive non-small-cell lung cancer. Methods: The chromatographic separation was carried out in an isocratic mode on an YMC ODS C18 column with a mobile phase consisting of methanol and water containing 0.1% orthophosphoric acid in the ratio of 50:50 v/v at a flow rate of 0.6 ml/min. The run time was maintained for 10 min and detection was monitored at 267 nm. The method involved reproducible liquid-liquid extraction of drug from human plasma using diethyl ether as extracting solvent. Results: CRZ and internal standard retention times were 6.86 and 7.94 min, respectively. Calibration curves were linear over a concentration range of 20.41–2041.14 ng/ml with correlation coefficient 0.9994. The lower limit of quantification for CRZ in plasma was 20 ng/ml. No endogenous substances were found to interfere with the peaks of drug and internal standard. The intra- and inter-day precision was <9.0% and the accuracy ranged from 97% to 112% over the linear range. All stability studies showed that CRZ in plasma sample was stable. Conclusion: This method was found to be simple, selective, precise, accurate, and cost-effective. Hence, the method can be successfully applied to analyze the CRZ concentration in plasma samples for pharmacokinetic and bioequivalence studies.